Impact of Merger on Employee Morale: Evidence from Pakistan - Iqbal, Danish; Waseem, Syeda Nazneen (Pakistan Journal of Humanities and Social Sciences, 2023)
The goal of the study is to evaluate how employee morale has been impacted by mergers in Karachi's banking sector. An organization must have good morale to be successful. Regardless of the size or sector of the company, high morale will boost output, job satisfaction, and absenteeism. A descriptive research design was used in the study to collect data from the targeted banks. The goal of the study is to evaluate how employee morale has been impacted by mergers in Karachi's banking sector. This is a quantitative analysis paper. The data for the paper was obtained from primary sources, such as questionnaires. To assess the impact of the data, statistical software SPSS was used. There were two variables dependent (Employee Morale) and independent variables (Job Satisfaction, Absenteeism and Employee Confidence). The study's participants were banks. The findings indicated that there was a substantial relationship between the variables, and the analysis employed Pearson correlation and Cronbach Alpha for each questionnaire. To see the individual effects of the sample, the frequency distribution was used. Topics related to this were also researched in specific literature. The last portion of this paper is the recommendation and conclusion.